2008
DOI: 10.1143/apex.1.077004
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Microspectroscopy Characterization of AlN Single Crystals

Abstract: Basic acoustic properties of AlN single crystal Y -cut and Z -cut plates, grown by the physical vapor transport method, were evaluated using ultrasonic microspectroscopy (UMS) technology. A method of determining the acoustical physical constants with two specimens was developed by measuring the velocities of longitudinal and shear waves and leaky surface acoustic waves (LSAWs). We obtained accurate bulk-wave velocities, LSAW velocities and their distributions in the specimen surfaces, and the density with grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…These elastic constants c 66 , c 11 and c 33 D were determined by the ultrasonic microscopy and Lamb wave devices. Here, we calculated the velocity values from the elastic constant reported by Tanaka's group by assuming that the mass density ρ is 3260 kg/m 3 [6]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These elastic constants c 66 , c 11 and c 33 D were determined by the ultrasonic microscopy and Lamb wave devices. Here, we calculated the velocity values from the elastic constant reported by Tanaka's group by assuming that the mass density ρ is 3260 kg/m 3 [6]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our group first reported the softening of longitudinal wave velocities (c 33 D /ρ) 1/2 . A 30-40% decrease of the velocity compared the single crystalline AlN was observed in the ScAlN films [5,6]. Moreira et al also reported the decreasing of elastic constants c 33 E in ScAlN film bulk acoustic resonators (FBARs) with Sc concentrations of 0-15% [7].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Theoretical conversion efficiency curves were simulated using Mason's equivalent circuit model. 20 The density q and the dielectric constant e 33 reported for an AlN single crystal 24 were used in this model, and the longitudinal wave velocity in this model was set to 75% of that of an AlN single crystal. 24 The fundamental mode acoustic resonance was excited around 2 GHz, and the excitation of a second-overtone mode acoustic resonance was not observed in both resonators.…”
Section: -mentioning
confidence: 99%
“…The velocity of the Sc 0.41 Al 0.59 N film near the phase boundary was 8020 m/s, which is 72% of 11132 m/s, the value for an AlN single crystal. 17 Figure 1(d) shows k t 2 as function of the Sc concentration. The solid circles show k t 2 extracted from the HBARs (including a substrate).…”
mentioning
confidence: 99%